When your MR linac is down: Can an automated pipeline bail you out of trouble?. (November 2021) - Placidi, L.; Cusumano, D.; Alparone, A.; Boldrini, L.; Nardini, M.; Meffe, G.; Chiloiro, G.; Romano, A.; Valentini, V.; Indovina, L.
Highlights: MRgRT system fail requires transferring in treatment patients to a conventional linac. Transfer requires several manual steps, it is time consuming and prone to errors. Automated pipeline is proposed to shift patients from MR-Linac a conventional linac. Automated plans were evaluated by dosimetric, planning and quality parameters. Fast and accurate generation of automatic treatment plans has been achieved. Abstract: Purpose: The unique treatment delivery technique provided by magnetic resonance guided radiotherapy (MRgRT) can represent a significant drawback when system fail occurs. This retrospective study proposes and evaluates a pipeline to completely automate the workflow necessary to shift a MRgRT treatment to a traditional radiotherapy linac. Material and methods: Patients undergoing treatment during the last MRgRT system failure were retrospectively included in this study. The core of the proposed pipeline was based on a tool able to mimic the original MR linac dose distribution. The so obtained dose distribution (AUTO) has been compared with the distribution obtained in the conventional radiotherapy linac (MAN). Plan comparison has been performed in terms of time required to obtain the final dose distribution, DVH parameters, dosimetric indices and visual analogue scales scoring by radiation oncologists. Results: AUTO plans generation has been obtained within 10 min for all the considered cases. All AUTO plans were found to be within clinical tolerance, showing a mean target coverage variation of 1.7% with a maximum value of 4.3% and a minimum of 0.6% when compared with MAN plans. The highest OARs mean variation has been found for rectum V60 (6.7%). Dosimetric indices showed no relevant differences, with smaller gradient measure in favour of AUTO plans. Visual analogue scales scoring has confirmed comparable plan quality for AUTO plans. Conclusion: The proposed workflow allows a fast and accurate generation of automatic treatment plans. AUTO plans can be considered equivalent to MAN ones, with limited clinical impact in the worst-case scenario.